HUBUNGAN MOTIVASI BERPRESTASI, PENYESUAIAN DIRI DAN PERANAN LAYANAN BIMBINGAN KONSELING DENGAN PRESTASI BELAJAR SISWA - SUNARMI , SUNARMI (2011)
Learning achievement in academic activity is avery important thing because it is the result of learning activities which are identified by the changes of knowledge, understanding, attitude and behaviour skill, capabiliity, ability of reacting, power of conceiving and aspects in the leaners them selves. Learning achievement in influenced by many things, among others are motivation to gain achievement, self adjustment and the role of guidance counseling. This research aims to know the relation of motivation of achievement, adjustment and role of tuition service of counseling with achievement of student learning. The hypotesis that there is correlation among achievement motivations, adjustment and role of guidance counseling with achievement of learning This research subject are students SMP N I Nogosari Boyolali which having the age between 12 to 15 years that amounts to 70 students of them with the cluster random sampling technique. Data collections technique is done by using motivation of achievement questionaire, self adjustment and role of guidance of counseling of student learning achievement and document which student value student. Data is analysed by regression. The results from the regression are: 1) There is a very significant correlation between interest motivation of achievement, adjustment and role of guidance counseling has significant influence to achievement of learning, 2) There is a positive correlation between the significant interest achievement motivation with achievement of learning, 3) There is a positive correlation between the significant interest adjustment with achievement of learning. 4) There is a positive correlation between the significant interest role of guidance counseling with achievement of learning. Based on the result of data analysis it can be concluded that : the proposed hypotetesis is accepted or proven. The result of the regression analysis is that there is correlation among achievement motivations, self adjustment and role of guidance of counseling with achievement of learning.This figure comes from effective countribution of achievement motivations, adjustment and role of guidance counseling with achievement of learning scores 97, 9% the other 2,1% come from other factors.